Comparative Analysis of Innovative Development Strategies of Fuel and Energy Complex of Ukraine and the EU Countries: International Experience - Redko , Kateryna; Borychenko , Olena; Cherniavskyi , Anatolii; Saienko , Volodymyr; Dudnikov, Serhii (International Journal of Energy Economics and Policy, 2023)
The European Union is pursuing an ambitious energy policy to reduce the emission of pollutants into the environment and achieve complete decarbonization by 2050. According to the approved Green Deal, each European state had to introduce its own energy strategy based on its own economic, social, climatic, and climatic conditions. In the process of European integration, Ukraine has developed its own strategies that meet the principles of European government policy. The analysis of the experience of implementation of energy strategies of different member states of the European Union will have a positive impact on the process of implementation of the new energy policy in Ukraine. According to this, a comparative analysis of strategies and the state of the fuel and energy complex of France, Austria, Poland, which have common features with the energy system of Ukraine. As a result of the study, it was found that the process of decarbonization should be gradual. Abrupt changes can lead to negative consequences in economic and social aspects. The information obtained can be useful for energy reforms in Ukraine.